Environmental food claims – legal aspects - Wojciechowski, Paweł (Przegląd Prawa Rolnego, 2023)
The article proposes a definition of environmental claims made on food, it identifies the objectives of food law in respect of such claims, and discusses the relevant regulation of both food law and consumer law. The author points out that in view of the widespread unreliable use of environmental claims, the adoption of a regulation setting out a framework for the use of this type of claim in relation to food is highly desirable as it might contribute to the more effective implementation of the objectives of food law.